1975
DOI: 10.1111/j.1600-051x.1975.tb01724.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of benzethonium and zinc chloride mouthrinses on human dental plaque and gingivitis

Abstract: In a double-blind study the plaque- and gingivitis-inhibiting capacities of three aqueous mouthrinse solutions of benzethonium chloride, zinc chloride, and benzethonium chloride combined with zinc chloride were compared to those of a placebo mouthrinse. Forth-three adults with clean teeth and healthy gingiva were randomly assigned to the treatment and control groups. All participants received an initial prophylaxis. Assessments of plaque and gingivitis were made before and after a 10-day test period. During th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…beagles did not affect its efficacy with respect to plaque reduction. The results reported in this paper confirm those of Compton and Beagrie (1975) who showed that 0.075 percent BTC was effective in reducing dental plaque and gingivitis in humans.…”
Section: Resultssupporting
confidence: 90%
“…beagles did not affect its efficacy with respect to plaque reduction. The results reported in this paper confirm those of Compton and Beagrie (1975) who showed that 0.075 percent BTC was effective in reducing dental plaque and gingivitis in humans.…”
Section: Resultssupporting
confidence: 90%
“…min. The strips were then soaked in freshly In contrast, Compton and Beagrie (1975) collected, wax-stimulated, human whole found no effect when a mouthwash contain-saliva (WSS) for 20 min and then placed on ing 0.22% zinc chloride solution (16.4 mM hooks of nichrome wire inserted into the zinc) was used for 10 days. However, since it underside of rubber bungs.…”
mentioning
confidence: 99%
“…In addition, elementary students are provided instant hand sanitizers containing QACs to decrease the spread of illness and reduce rates of absenteeism [12]. QACs are being increasingly incorporated into contemporary products that are utilized orally, such as mouth wash, applied to the skin or eyes or administered as a nasal spray [13–20]. …”
Section: Introductionmentioning
confidence: 99%